A 'central paradox': Judicial decision-making in cases of sexual offending by young people. Issue 1 (March 2023) - Parker, Megan; Richards, Kelly
Very little has previously been documented about judicial decision-making in relation to young people who commit sexual offences. This article begins to address this gap by examining judicial decision-making in cases of young people with sexual offence convictions in one Australian jurisdiction. Employing a qualitative content analysis of sentencing remarks and judgments, it investigates how judicial decision-makers construct this cohort of young people given the 'central paradox' that young offenders are typically regarded as reformable while sexual offenders are not. Results of the study make an original contribution toward understanding judicial constructions of both sex offenders and youth offenders, and in particular toward the very under-researched area of judicial constructions of youthful sexual offenders specifically. In doing so, the study offers a much-needed evidence base that can contribute to a better understanding of judicial reasoning.